Bacterial consumption by nematodes is disturbed by the presence of polystyrene beads: The roles of food dilution and pharyngeal pumping. (15th March 2021) - Rauchschwalbe, Marie-Theres; Fueser, Hendrik; Traunspurger, Walter; Höss, Sebastian
Abstract: Microplastics (MPs; <5 mm) released into freshwaters from anthropogenic sources accumulate in sediments, where they may pose an environmental threat to benthic organisms, such as nematodes. Several studies have examined the effects of nano- and microplastics on the nematode Caenorhabditis elegans, whereas reduced food availability was suggested as a possible explanation for the observed inhibitory effects. Therefore, this study should clarify whether micro-beads of different sizes (1.0 and 6.0 μm in diameter) and materials (polystyrene PS, silica) are able to interfere with the feeding of C. elegans on its bacterial diet ( Escherichia coli ), and, by this, lowering its consumption rate within 7 h of exposure. Moreover, it was examined whether an inhibited bacterial consumption was caused by a reduction of the nematode's pumping rate, as a primary indicator of food ingestion. Bacterial consumption by C. elegans was significantly decreased in the presence of 1.0- and 6.0-μm PS beads (49–67% lower bacterial consumption compared to control), whereas in the presence of 1.0-μm silica beads feeding was not impeded. Interestingly, the pumping rate was significantly lower in the presence of non-ingestible 6.0-μm PS beads with 161 ± 16 pumps min −1, while it was largely unchanged for nematodes exposed to ingestible 1.0-μm PS beads with 205 ± 12 pumps min −1, compared to control conditions with 210 ± 18 pumps min −1, respectively. As reduced bacterial consumption leads to generally lower energy reserves in C. elegans, these results allow to link observed inhibitory effects of MPs on the nematodes to a lower food availability. Such indirect, food-web related, effects of MPs should raise concern of ecological consequences in natural habitats, where temporal food deficiencies can occur. Consequently, disturbances in food availability and feeding efficiency should be regarded as important parameters in environmental risk assessments focusing on MPs. Graphical abstract: Image 1 Highlights: Polystyrene (PS) beads significantly limited bacterial consumption of C. elegans . Reduced pharyngal pumping by 6-μm PS beads partly explained lower consumption. 1-μm PS beads reduced consumption by diluting the bacteria. 1-μm silica beads had no impact on bacterial consumption. Results confirm the link of inhibitory effects of MP to reduced food availability. Abstract : Capsule: Bacterial consumption by Caeonorhabditis elegans is disturbed by the presence of polystyrene beads of ingestible and non-ingestible size.